Getting Help from 2-1-1: A Statewide Study of Referral Outcomes. Issue 42 (26th May 2016) - Boyum, Sonia; Kreuter, Matthew W.; McQueen, Amy; Thompson, Tess; Greer, Regina
ABSTRACT: The 2-1-1 information and referral helpline connects economically vulnerable Americans with needed health and social services in their communities. This longitudinal study followed a random sample of 2-1-1 callers in Missouri ( n = 1, 235) to determine the results of the referrals they received. One month after calling 2-1-1, most remembered receiving (93%), tried contacting (91%), and reached (82%) at least one referral they received. Far fewer (36%) received assistance from the referral, ranging from 17% for housing assistance to 67% for food assistance. Callers receiving assistance were much more likely than those not receiving assistance to report at the one-month follow-up that their problem had been resolved (OR = 3.0, 95% CI = 2.2, 4.1), although this was less true among callers with multiple unmet basic needs. Findings explain how 2-1-1 helps callers resolve problems but also helps them identify missed opportunities in the current system. Future research could elucidate how 2-1-1 callers resolve problems; it could also find ways to improve outcomes for the most disadvantaged 2-1-1 callers.